2016
DOI: 10.1016/j.telpol.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Ladder of Investment in Central and Eastern European countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…However, not all territories that have been able to facilitate development of fiber-optic networks relied on governmental aid, and, moreover, the population density, which has a significant impact on the deployment of FTTx infrastructure, of the east of Europe is noticeably lower than the population density of the Asian frontrunners. Serdarević et al (2016) expose dissimilarity of telecommunications development in Western European countries and Central and Eastern European (CEE) 6 countries of the EU and clarify why newcomers of telecommunications markets in CEE countries were able to invest in their own networks without reliance on the incumbents' facilities. The examination of the Bulgarian case by Rood (2010) contributes to the explanation of the superiority of FTTx development of some of the Eastern European countries compared with the more economically developed parts of the EU and points out Besthetical policies^as one of the reasons Bwhy Europe trails other countries in new infrastructure roll out.T he results of these studies of the Eastern European cases correspond with some of the features of the evolution of telecommunications in Russia: the rollout of FTTx networks through the aerial deployment of fiber-optic cables, the underdevelopment of the incumbents' infrastructure at the moment of the start of the reform accompanied by the shortage or even lack of cable TVoperators in the markets and the high unsatisfied demand.…”
Section: Bcompetitive Order^vs Bordered Competitionî N Telecommunicamentioning
confidence: 95%
“…However, not all territories that have been able to facilitate development of fiber-optic networks relied on governmental aid, and, moreover, the population density, which has a significant impact on the deployment of FTTx infrastructure, of the east of Europe is noticeably lower than the population density of the Asian frontrunners. Serdarević et al (2016) expose dissimilarity of telecommunications development in Western European countries and Central and Eastern European (CEE) 6 countries of the EU and clarify why newcomers of telecommunications markets in CEE countries were able to invest in their own networks without reliance on the incumbents' facilities. The examination of the Bulgarian case by Rood (2010) contributes to the explanation of the superiority of FTTx development of some of the Eastern European countries compared with the more economically developed parts of the EU and points out Besthetical policies^as one of the reasons Bwhy Europe trails other countries in new infrastructure roll out.T he results of these studies of the Eastern European cases correspond with some of the features of the evolution of telecommunications in Russia: the rollout of FTTx networks through the aerial deployment of fiber-optic cables, the underdevelopment of the incumbents' infrastructure at the moment of the start of the reform accompanied by the shortage or even lack of cable TVoperators in the markets and the high unsatisfied demand.…”
Section: Bcompetitive Order^vs Bordered Competitionî N Telecommunicamentioning
confidence: 95%
“…Уже после завершения активной фазы «либерализации» отрасли многие исследователи применяемых подходов в постдерегулированном регулировании телекоммуникаций стали обращать внимание на то, что ключевые показатели сектора в наиболее развитых странах Европы оказались гораздо хуже, чем в некоторых странах Восточной Европы [Lemstra, Melody, 2014;Rood, 2010;Serdarević et al, 2016]. Особенно парадоксальным выглядит показатель развития оптоволоконных сетей связи, даже несмотря на то что европейские разработчики политики обозначили его в качестве одного из приоритетных ориентиров.…”
Section: альтернатива «управляемой конкуренции»unclassified
“…Это пытались объяснить, указывая как на некоторые ошибки в применяемых методах регулирования [Serdarević et al, 2016], так и на экономическую отсталость посткоммунистических территорий, которая создавала преимущества для бедных стран перед богатыми [Briglauer, Gugler, 2013]. Не вступая в дискуссию о подобных теориях, стоит отметить, что они не предлагают альтернативы вышеизложенным представлениям о том, что конкуренцию необходимо развивать при помощи запретов и ограничений.…”
Section: альтернатива «управляемой конкуренции»unclassified
See 1 more Smart Citation
“…The current situation in the European market speaks in favor of this claim: the big companies from the advanced European economies have managed to take control over the industry in many less developed parts of the continent 2 , but it does not mean that small European countries were unable to develop the industry without such aid. The recent studies show that some Central and Eastern European countries not only demonstrated the higher level of competition and the presence of small and medium-sized enterprises in the industry during the first decade of the XXI century, but also have been able to leapfrog the most advanced economies of the EU in the development of fiber-optic infrastructure (Lemstra & Melody, 2014;Serdarević et al, 2016;Rood, 2010).…”
Section: Transformation Of the Landscape Of The Telecommunications Inmentioning
confidence: 99%